Sessile Serrated Adenoma With Dysplasia of the Colon: A Retrospective Pathology Review Focusing on Subtypes. Issue 2 (20th September 2021) - Batts, Kenneth P; Cinnor, Birtukan; Kim, Adam; Stickney, Emily; Burgart, Lawrence J
Abstract: Objectives: Sessile serrated adenomas with dysplasia (SSADs) of the colon are transitional lesions between sessile serrated adenomas (SSAs) and a subset of colorectal adenocarcinomas. We wished to gain insight into the relative percentages and significance of SSAD subtypes. Methods: Retrospective (2007-2012) clinicopathologic review of colorectal polyps initially regarded as having mixed serrated and dysplastic elements. SSADs were subdivided into those with cap-like adenomatous dysplasia (ad1), non-cap-like adenomatous dysplasia (ad2), serrated dysplasia (ser), minimal dysplasia (min), and dysplasia not otherwise specified (nos). MLH1 immunostaining was performed on many. Results: SSADser (7.7%) had a greater propensity for right colon, women, and MLH1 loss vs the entire cohort. SSAad1 (11.6%) had the least female preponderance, was least likely to have MLH1 loss, and was most likely to affect the left colorectum. SSAD with MLH1 loss was associated with an increased burden of SSAs in the background colon ( P = .0003) but not tubular adenomas or hyperplastic polyps. Most SSADs (ad2 and nos groups, 80% combined) showed difficult-to-classify dysplasia, intermediate MLH1 loss rates, and intermediate clinical features. Conclusions: While some trends exist, morphologically subclassifying SSADs is probably not justified in routine clinical practice. MLH1 loss portends a greater burden of SSAs in the background colon.